Breastfeeding in Western Saudi Arabia: a prospective cohort study - Al Juaid, Daifellah A M (Curtin University, 2016)
A cohort of 578 of mothers and their infants from Western Saudi Arabia were followed for six months to document infant feeding practices. Breastfeeding was initiated by 80% of mothers, but only 48.6% were exclusively breastfeeding at discharge. The ‘any breastfeeding’ rate declined to 46% at six months. Most mothers (71.3%) introduced some infant formula before six weeks of age. Younger age, primi-parity, higher socio-economic status, obesity and depression were associated with lower breastfeeding rates.